Frecuencia de microalbuminuria en gestantes atendidas en el Hospital Regional “Miguel Ángel Mariscal Llerena” Ayacucho- agosto 2017 - enero 2018. - Galván Huaman, Ketty Edna (2020)
Micro albuminuria is the elimination of albumin in the urine, during pregnancy it can cause serious complications such as pre eclampsia, which is characterized by the increase in blood pressure during pregnancy, which is a very common health problem because it causes an increase in maternal and perinatal morbidity and mortality. Albumine excreted in the urine has a sensitivity of 88.9% as a predictor of pre eclampsia. The research was conducted, with the objective of determining the frequency of micro albuminuria in pregnant women who attended the Regional Hospital De Ayacucho, "Miguel Ángel Mariscal Llerena" -Ayacucho- from August 2017 to January 2018. A descriptive cross-sectional study was carried out in 221 pregnant women who attended the consultation in the Gynecology Obstetrics service of the Regional Hospital of Ayacucho “MMLL”. The data were obtained through surveys, with the informed consent, the requested urine samples were collected. At pregnant women, the determination of microalbuminuria was carried out using the quantitative method of immunoturbidimetric assay, in automated equipment BS-300. For data processing, SPSS version 23 and Microsoft Excel were used. Of the total of 221 pregnant women under study, 13.1% presented positive micro albuminuria between 20 to 100mg / l of which 3.9% from 15 to 25 years of age; 55.6% from 36 to 45 years and 1% in the age range from 26 to 35 years, with respect to gestation age 55.2% was presented between 36 and 40 weeks followed by 20.7% in weeks 20 to 25 and 31 to 35 weeks, The association between MALB and gestational age was demonstrated.